Miocene Provenance Changes in Taiwan Caused by Southward Input of Sediments From East China Sea Basin - Fu, Xiaowei; Hu, Lichen; Zhu, Weilin; Huang, Xiangtong; Feng, Kailong; Zhou, Zengyuan (Frontiers in Earth Science, 2022)
The Cenozoic sediments in marginal basins of East Asia ultimately reflected coupling between the tectonics, landscape evolution, and drainage reorganization. Recently, the provenance of Miocene sediments in the East China Sea Basin (ECSB) and Taiwan has been in hot debate, and several models were proposed to interpret the provenance changes. Most of them are related to river reorganization in East Asia and highly relied on detrital zircon U-Pb dating. In this study, a large number of detrital zircon U-Pb ages of Miocene sediments from the ECSB, Taiwan region, and the potential source areas have been compiled for quantitative provenance analysis. The results suggested that all the early–middle Miocene sediments in Taiwan and the ECSB were closely linked to North China and the Korean Peninsula. Over 80% sediments in Taiwan were delivered from the ECSB whose sediments were predominantly contributed by North China and the Korean Peninsula (70%). However, for the late Miocene to Quaternary sediments in the ECSB, the contribution of the Yangtze River system was 72%, which indicates distinct reorganization of river networks and initial formation of the Yangtze River in the late Miocene. The quantitative provenance analysis together with southward environmental changes from dominantly fluvial sediments in the northern and middle ECSB to shallow marine sediments in Taiwan region suggested that the early–middle Miocene sediments of Taiwan were mainly sourced from the North China and the Korean Peninsula by passing the ECSB. Thus, these sediments in Taiwan region would experience the river–delta–shallow marine route from the ECSB to Taiwan region.